199 Temporally Coordinated Deep Brain Stimulation in the Dorsal and Ventral Striatum Synergistically Enhances Associative Learning. (August 2015) - Kwon, Churl-Su; Katnani, Husam; Patel, Shaun; Abdel-Aziz, Samer; Gale, John; Eskandar, Emad N.
Abstract : INTRODUCTION: Considerable evidence points to cortico-striato-thalamo-cortical circuits in cognitive, limbic, and motor functions. Specifically, the connections between caudate, nucleus accumbens (NAc), and prefrontal cortex have been implicated in behavioral learning and motivation. Precisely timed stimulation of the caudate during a behavioral task enhances learning beyond baseline in normal primates. We test the overarching hypothesis that combined intermittent stimulation of the caudate and NAc leads to enhanced learning. Our specific hypothesis is that there are 2 streams of information processing in the anterior striatum, dorsal and ventral, that perform complementary but different roles. We believe that the dorsal stream, which includes the caudate, is involved in the executive aspect of associative learning, whereas the ventral stream, which includes the NAc, is involved in providing the motivation for the performance of learned behavior. METHODS: Two primates were trained to perform a visuomotor learning task, wherein the animal was required to learn, by trial-and-error, to associate arbitrary visual images with specific movements in 1 of 4 directions. The monkeys used a touch screen to associate the visual image with 1 of 4 targets displayed in the periphery. The subjects received stimulation at time points critical to learning related changes. RESULTS: Significant associative learning was seen with caudate stimulation at positive feedback compared to no stimulation. A further increased synergistic effect in learning was seen with dual stimulation of NAc (before image presentation) and caudate (at positive feedback). Reaction time was significantly quicker with dual stimulation. Stimulation of each brain region alone or at different time points did not generate the same effect. CONCLUSION: Enhancing visuomotor performance may be beneficial to patients who have cognitive-motor deficits caused by traumatic brain injury. Deep brain stimulation strategies augmenting learning and motivational processes could be used in humans to enhance a broad range of functions including gross motor movements and decision making.